Highly selective and durable of monodispersed metal atoms in ammonia production. (April 2022) - Zheng, Zhiqiang; Qi, Lu; Xue, Yurui; Li, Yuliang
Highlights: A graphdiyne-based zerovalent copper atomic catalysts is synthesized for highly efficient NO3 − -to-NH3 conversion. The incomplete charge transfer between Cu atoms and GDY produces continuous high performances for the catalysis. The atomic catalysts show excellent ammonia yield rate and Faradaic efficiency at ambient temperatures and pressures. Graphical Abstract: Summary of the research: The highly dispersed zero-valent copper atomic catalysts anchored on graphdiyne exhibits high NH3 yield rate, Faradaic efficiency, as well as excellent stability for electrochemical NO3 - -to-NH3 conversion under ambient condition. Our results demonstrated such excellent properties originated from the highly dispersed active sites and incomplete charge transfer behaviors between metal atoms and graphdiyne in the catalyst process. ga1 Abstract: Electrochemical synthesis of ammonia under environmental conditions is a beautiful dream of scientists and entrepreneurs, and has been regarded as an ideal alternative strategy to traditional Haber-Bosch process. In this study of synthetic ammonia, we rationally consider the defects of the current catalysts and propose innovative preparation methods. For the first time, we synthesized independent, highly dispersed zero-valent copper atomic catalysts which were uniformly distributed on 2D graphdiyne (Cu 0 /GDYNA). This catalyst was used for electrochemical NO3 - -to-NH3 conversion. After dozens of rigorous experiments, an exciting result are presented that the Cu 0 /GDYNA showed the highest NH3 yield rate (YNH3 ) of 15.45 mmol h −1 cm −2 and the maximal ammonia Faradaic efficiency (FE) of 81.25% at ambient temperatures and pressures. Furthermore, the Cu 0 /GDYNA could continuously catalyze the ammonia production over a consecutive 36-cycle electrolysis with almost no loss of catalytic performance. The excellent electrocatalytic properties of atomic catalysts show that the incomplete charge transfer behavior between metal atoms and GDY produces continuous high activity, promotes ammonia production rapidly selectively suppresses inhibitory by-products, and achieves ultra-high ammonia yield and FE.